Effect of a Nurse-Managed Telemetry Discontinuation Protocol on Monitoring Duration, Alarm Frequency, and Adverse Patient Events. Issue 2 (April 2017) - Perrin, Keisha; Ernst, Neysa; Nelson, Terry; Sawyer, Melinda; Pfoh, Elizabeth; Cvach, Maria
Abstract : Telemetry monitoring is a limited resource. This quality improvement project describes a nurse-managed telemetry discontinuation protocol aimed at stopping telemetry monitoring when it is no longer indicated. After implementing the protocol, data were collected for 6 months and compared with a preintervention time frame. There was a mean decrease in telemetry monitor usage and a decreased likelihood of remaining on a telemetry monitor until discharge. A nurse-managed telemetry discontinuation protocol was effective in decreasing overmonitoring and ensuring telemetry availability. Abstract : Supplemental Digital Content is Available in the Text.